2008
DOI: 10.1038/sj.bjc.6604316
|View full text |Cite|
|
Sign up to set email alerts
|

Acquisition of biologically relevant gene expression data by Affymetrix microarray analysis of archival formalin-fixed paraffin-embedded tumours

Abstract: Robust protocols for microarray gene expression profiling of archival formalin-fixed paraffin-embedded tissue (FFPET) are needed to facilitate research when availability of fresh-frozen tissue is limited. Recent reports attest to the feasibility of this approach, but the clinical value of these data is poorly understood. We employed state-of-the-art RNA extraction and Affymetrix microarray technology to examine 34 archival FFPET primary extremity soft tissue sarcomas. Nineteen arrays met stringent QC criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 42 publications
(49 reference statements)
5
74
1
1
Order By: Relevance
“…We demonstrated that FFPE tissue has high sensitivity, specificity and accuracy in comparison with deep-frozen tissue for HPV detection in LSCC. These findings confirm and expand the results of studies of other authors for lung and cervical cancers [16][17][18]. Farragher et al [16] observed a remarkably high level of present cells in both frozen and FFPE samples.…”
Section: Discussionsupporting
confidence: 82%
“…We demonstrated that FFPE tissue has high sensitivity, specificity and accuracy in comparison with deep-frozen tissue for HPV detection in LSCC. These findings confirm and expand the results of studies of other authors for lung and cervical cancers [16][17][18]. Farragher et al [16] observed a remarkably high level of present cells in both frozen and FFPE samples.…”
Section: Discussionsupporting
confidence: 82%
“…21 However, significant improvements have been made in RNA isolation and amplification-a series of reports have suggested that gene profiling on formalin-fixed and paraffinembedded tissue material is now feasible. One study 7 concluded that although the sensitivity of formalin-fixed and paraffin-embedded tissue profiling was low (B50%), when compared with frozen tissue, the specificity (95%) and positive predictive value (92%) were high. In another study, 18 high correlation (R 2 between 0.82 and 0.89) of profiling data between frozen and formalin-fixed and paraffin-embedded tissue tissue was identified in tumors from the lung and colon.…”
Section: Discussionmentioning
confidence: 99%
“…This traditional view has recently been challenged, and several groups have reported quantitative gene expression and microarray profiling data from formalin-fixed and paraffin-embedded tissue blocks. 7,8 The goal of this study was to explore signal transduction pathways and gene expression profile in three common gastrointestinal neuroendocrine tumors: rectum, small intestine and pancreas, and assess the heterogeneity in the signaling pathways across these tumors. Identification of novel signaling pathway may uncover potential druggable targets.…”
mentioning
confidence: 99%
“…[30][31][32][33][34]57,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Although sensitivity is low, high specificity and positive predictive value suggest that transcript detection is reliable from formalin-fixed paraffin-embedded tissue. 33 Although RNA isolation techniques from formalin-fixed paraffin-embedded tissues have improved, problems remain, largely because of the greater fragmented nature of RNA in formalin-fixed paraffin-embedded tissue. 30,32,75,78 Magnitudes of differential expression are often higher in formalin-fixed paraffin-embedded tissue than in fresh frozen samples, because of the increased background noise; this increases the odds of false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…The search was limited to cases from the previous 3 years, as early literature indicated that this period of storage did not adversely affect RNA extraction for microarray analysis in formalin-fixed paraffinembedded blocks. 30,33,34 All slides were re-reviewed by three authors (SS, SB and SD) and appropriately categorized based on histological and immunohistochemical criteria set forth by the Armed Forces Institute of Pathology, World Health Organization and Hornick and Fletcher's reviews of neurothekeomas and cellular fibrohistiocytic tumors (Table 1). 22,[27][28][29]35,36 Exclusion criteria included cases with scant tissue remaining in the block and cases without unanimous agreement on the definitive diagnosis.…”
Section: Methodsmentioning
confidence: 99%